2021
DOI: 10.3389/fendo.2021.663636
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Radiofrequency Ablation for Bilateral Papillary Thyroid Microcarcinoma

Abstract: ObjectiveTo investigate the long-term clinical results of radiofrequency ablation (RFA) for bilateral papillary thyroid microcarcinoma (PTMC).Materials and MethodsFrom October 2014 to February 2018, 47 patients (37 females, 10 males, mean age 43.39 ± 9.26 years) with 100 bilateral PTMC (mean volume 75.22 ± 73.87 mm3) treated by RFA were included in this retrospective study. Bilateral PTMC was defined as at least one tumor located in the contralateral lobe. Patients were followed up at 1, 3, 6, 12 months and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…According to the 8th AJCC/TNM Mortality Risk System and ATA Risk Stratification (14,94), bilateral PTMC is classified as stage I with a low risk of recurrence. The safety and efficacy of RFA for bilateral PTMC was analyzed in 47 cases (75). The results showed a complete disappearance rate of 92%, but recurrence was observed in two patients.…”
Section: Number Of Ptcsmentioning
confidence: 99%
“…According to the 8th AJCC/TNM Mortality Risk System and ATA Risk Stratification (14,94), bilateral PTMC is classified as stage I with a low risk of recurrence. The safety and efficacy of RFA for bilateral PTMC was analyzed in 47 cases (75). The results showed a complete disappearance rate of 92%, but recurrence was observed in two patients.…”
Section: Number Of Ptcsmentioning
confidence: 99%
“…Bilateral multifocality was more aggressive than unilateral multifocality, but it was not an independent prognosis factor ( 40 ). In 2021, one study preliminarily evaluated the efficacy and safety of RFA for 47 patients with 100 bilateral PTMCs, and the incidences of lymph node metastasis and recurrence were 2.13% and 4.26%, respectively ( 17 ), which were not higher than the currently known incidences ( 37 , 39 ). In this study, we included 7 (58.3%) patients with bilateral multifocal PTMCs.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, some studies with long-term follow-up revealed no significant differences in tumor size increase, lymph node metastasis, and extra-thyroidal invasion between unifocal and multifocal PTMC ( 35 , 36 ). Although the current guidelines for the thermal ablation of PTMC did not recommend ablation of multifocal PTMC, several studies had been conducted on the clinical outcomes of RFA for multifocal PTMC ( 16 , 17 ). A large cohort study evaluated the efficacy of RFA in 432 patients with unifocal PTMC and 55 patients with multifocal PTMC, and the results showed that multifocality had little effect on patient outcomes ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PTMC with no evidence of extra thyroid expansion and lymph node metastasis, thermal ablation has become the main treatment for primary low-risk PTMC [ 31 33 ]. Compared with conventional surgery, thermal ablation significantly reduced the volume of primary tumor, had fewer postoperative complications, had a lower incidence of other serious complications, avoided complications related to general anesthesia, and achieved rapid recovery [ 5 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%